2019
DOI: 10.1039/c9nr05533a
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-insensitive colorful meta-holography employing anisotropic nanostructures

Abstract: A polarization-insensitive colorful meta-hologram was realized using anisotropic elliptical nanoholes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…To design a metasurface holographic device (phase only or complex), discrete phase shifts are the crucial information that can be tailored by engineering the spatial dimensions and/or orientation of the meta-elements depending upon the input/ output polarization of the light. Several polarization-dependent and independent metasurface holograms have been reported for linearly polarized light [11,14,[43][44][45][46][47] . For CP light, most meta-holograms involving the spin of light display the holographic image on the cross polarization, making them sensitive to handedness of the incident light [48][49][50][51][52] .…”
Section: Spin-insensitive Meta-hologrammentioning
confidence: 99%
See 1 more Smart Citation
“…To design a metasurface holographic device (phase only or complex), discrete phase shifts are the crucial information that can be tailored by engineering the spatial dimensions and/or orientation of the meta-elements depending upon the input/ output polarization of the light. Several polarization-dependent and independent metasurface holograms have been reported for linearly polarized light [11,14,[43][44][45][46][47] . For CP light, most meta-holograms involving the spin of light display the holographic image on the cross polarization, making them sensitive to handedness of the incident light [48][49][50][51][52] .…”
Section: Spin-insensitive Meta-hologrammentioning
confidence: 99%
“…Polarization of the incident light plays a key role in light-matter interaction for wavefront manipulation; however, geometry of meta-elements makes the metasurfaces sensitive to the incident polarization of the light. There have been several efforts to realize singlelayered polarization-insensitive metasurfaces for wavefront engineering functionalities, e.g., meta-holograms, metalenses, and beam steering for linear and circular polarization [11][12][13][14][15][16] . For circularly polarized (CP) wavefront manipulation, these metasurfaces either use propagation phase or compound geometric and propagation phase to obtain the desired phase profiles on CP orthogonal polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion efficiency of such a design technique is theoretically limited to 50% . In other studies, amplitude manipulation-based polarization-insensitive metasurfaces are reported. , Such metasurfaces depict the holographic output in the near field of the metasurface, making them unsuitable for such biomedical packaging security applications. Therefore, there is a strong need to develop a new phase-manipulation-based polarization-insensitive metadevice designing technique that can break all of the aforementioned limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, owing to the unprecedented ability to modulate electromagnetic waves, metasurfaces can precisely manipulate the phase, amplitude, and polarization of the incident light with subwavelength dimensions [ 5 , 6 , 7 , 8 , 9 ], which pave a new path to encode and display multi-channel images [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Among them, nanoprinting and holographic images are emerging research fields.…”
Section: Introductionmentioning
confidence: 99%